Analysis of International Experiences in Special Orientation of Service Dogs (Based on the experience of training service dogs of the cytological service of the Russian Federation and the Republic of Latvia) - Karimjonova Munavvar Ibragimovna (Zien Journals, 2023)
In this article, the importance of canine service in the system of law enforcement bodies of the Republic of Uzbekistan, including the role and activity of the national canine center in the system of customs bodies, issues of organization of some shortcomings in the methodology of training service dogs to a general training course based on advanced international experiences are highlighted. Also, scientific proposals and recommendations are presented on the development and improvement of the training process of service dogs in order to ensure the economic security of our country, and to create new training methods based on advanced international experiences.
Keywords: ustoms activity; canine service; canine; service dogs